A Multimodal Radar-Ultrasound Imaging Concept for Improved Display of Concealed Objects - Ullmann, Ingrid; Körner, Georg; Adametz, Julian; Vossiek, Martin (IEEE Access, 2019)
Subsurface radar imaging provides an insight into hidden scenes: For example, in security screening, radar can be used for the detection of dangerous objects or contraband. In non-destructive testing, radar imaging also allows to find internal material defects such as cracks or contaminations. Object contours and internal structures appear as echoes in the radar receive signal. The strongest echo typically is the one from the test object’s surface. This echo can mask smaller echoes close to the surface and therefore, small inner structures may become invisible in the reconstruction image. To overcome this problem, we propose a novel concept to eliminate the surface echo in radar imaging. In contrast to existing surface elimination techniques, our approach can be used not only when screening objects with planar surfaces, but also on such that exhibit an unknown and possibly non-planar profile. Our approach is to combine radar and air-coupled ultrasound. Since air-coupled ultrasound cannot penetrate into solids, the receive signal only contains the echo from the test object’s surface. The core of our concept is to generate radar and ultrasound signals with the same characteristics, i.e. they are equal in amplitude and phase. Then, the ultrasound data can be subtracted from the radar data and the resulting signal will only contain the echoes of the inner structures. When processing this data, the reconstructed images are almost free of reflections from the surfac